Criminal Acts Participated in Demolition and Persecution in Kampung Bundar, Karang Baru District, Aceh Tamiang Regency (Analysis of Decision Number: 216/PID. B/2021/PN. KSP) - Zulkifli; Riza Zarzani (International Journal of Society and Law, 2024)
Violence, especially demolition, has become a troubling social phenomenon in society. This action is often carried out by a group of people in a high emotional state, triggering serious violations of the law. Demolition not only harms victims but also creates injustice in law enforcement. This study examines legal arrangements related to the crime of demolition in positive law and law enforcement in case Number 216/Pid.B/2021/Pn Ksp in Aceh Tamiang. This case involves the defendant who carried out the assault on the victim with the threat of punishment imposed by the court. The results of the study show that despite the regulations that govern it, the implementation of law enforcement still faces various obstacles, including the lack of evidence and the influence of social factors. This research aims to provide insight into the challenges in law enforcement and encourage public awareness to better appreciate the legal process as an alternative to conflict resolution.